PENERAPAN SISTEM BAGI HASIL DAN PERLAKUAN AKUNTANSI PEMBIAYAAN MUDHARABAH - Pertiwi, Petty Amalia; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTAlong with the sharia economic development, Islamic financial institutions are required to bemore optimal in managing their financial activities. This research is aimed to find out the procedures,the accounting treatment, and the calculation of Mudharabah with reference to SFAS No. 105. Thesubject of this research is Sharia Financial Service Cooperative (KJKS) Muamalah Berkah SejahteraSurabaya. The analysis technique has been done by using qualitative descriptive, in which the data hasbeen obtained from the company is analyzed and compared with the existing theories.The result of the research shows that KJKS Muamalah Berkah Sejahtera Surabaya has run theprocedure of mudharabah financing well, the process of providing information in terms of mudharabahfinancing has been done, pillars and terms of mudharabah financing has been fulfilled, mudharabahfinancing has been documented, and investment activities which has been financed is in accordancewith Islamic principles. Moreover, KJKS Muamalah Berkah Sejahtera Surabaya has implemented theaccounting treament and the calculation of profit sharing in accordance with the SFAS No. 105 quitewell in terms of recognizing, measuring, presenting and performing disclosure.Mudharabah financing recognition is carried out on the delivery of the capital, when the revenueacquisition of profit sharing, and the return mudharabah capital. The presentation of mudharabahfinancing in the financial statements on the balance sheet component on the next side of assets, profit /loss is presented in the form of grouping of revenues and expenses according to the characteristics oftransactions, and disclosures are presented in the recording to the financial statements.Keywords: Sharia Finance, Mudharabah financing, profit sharing.